Rethinking Graduate Employability in Context Discourse, Policy and Practice - Siivonen, Päivi; Isopahkala-Bouret, Ulpukka; Tomlinson, Michael; Korhonen, Maija; Haltia, Nina (Springer Nature, 2023)
This open access book offers critical, multidisciplinary analyses on graduate employability. The book examines employability at the macro, meso and micro levels: higher education policy, the labour market, higher education institutions, organisations, individuals and social groups, in European, North American and Australian contexts. The contributors provide social and contextual analysis of graduate employability as a theoretical concept, a discourse and policy imperative and a social and discursive practice. The volume also introduces novel methodological perspectives to study the process of graduate employability. There is an urgent need for comprehensive and unified critical perspectives on graduate employability, as such analyses have so far been scarce and often isolated. Besides filling this gap in the literature, the book will also serve as essential reading on courses that focus on graduate careers and employability as well as higher education policy and practice.